Impact of educational and religious homogamy on marital stability - Kornelius Kraft; Stefanie Neimann (Institute for the Study of Labor (IZA), 2009)
Using a rich panel data set from the German Socio-Economic Panel, we test whether spouses who are similar to each other in certain respects have a lower probability of divorce than dissimilar spouses. We focus on the effect of homogamy with respect to education and church attendance. Gary Becker's theory of marriage predicts that usually, positive assortative mating is optimal. Our results, however, suggest that homogamy per se does not increase marital stability but higher education and religiousness.
urn:nbn:de:101:1-20091026118
Keywords: I20; J12; 330; Divorce; homogamy; education; Ehe; Scheidung; Verhalten; Bildungsniveau; Religionsgemeinschaft; Deutschland